INFLUENCE OF SMI'S COMPETENCE TO IT ADOPTION THROUGH THE READINESS OF SMI IN ENTERING INTO INDUSTRIAL REVOLUTION 4.0 - Nilawati Fiernaningsih; widayani, anna (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2021)
The purpose of this edifying is to explain and analyze the influence of the competence ofsmall and medium industry actors to the adoption of IT through the readiness of small andmedium industries in entering the Industrial revolution of 4.0. This research uses aquantitative approach using explanatory research. The population of this research is thesmall and medium industry of the food and beverage sector in Blitar city totaling 2896 SMIactors. To determine the sample of the population, researchers used the formula of Yamaneto obtain a total number of respondents 97 people. The sampling technique of this researchis a random sampling technique with the number of samples taken proportionally followingthe number of SMI actors in Blitar City. The method of collecting data using questionnairesis distributed to respondents and is calculated on a Likert scale. Data is analyzed using thepath analysis using SPSS. Data analysis methods consist of instrument tests, descriptivestatistical analysis, inferential statistical analysis, and hypothesis testing with pathanalysis. The results of this study showed that the competency of SMI practitioners, SMIreadiness has a positive and significant influence on IT adoption